Psikiyatrik Vakalardan Esinlenen Edebi Eserlerde Kadın Karakterler Üzerine Bir İnceleme / An Investigation on Female Characters in Literary Works Inspired by Psychiatric Cases - Üçler, Fatma (Journal of History Culture and Art Research, 2018)
Abstract The aim of this study is to evaluate the text of psychiatric cases from a literary perspective. Based on the stories and therapies of her patients, Gülseren Budayıcıoğlu who is a psychiatrist presents them to the reader in her short stories and novel fictions. We will subject the works based on female characters to literary analysis. The author's first work, Madalyonun İçi, consists of short stories. The second work, Günahın Üç Rengi, basically contains three main stories. His third work, Hayata Dön, despite being a novel, displays cases of patients. In these works, the author reveals his identity as a doctor and the perception of reality is always open. The fourth work, Kral Kaybederse, is a technical novel fiction. In every work, woman is in the foreground. In her works, the effects of the damage on the psychology of the women and, as a psychiatrist, the authors’ approach to the problems and his guidance to the women on how to deal with these problems are included. Öz Bu çalışma, edebiyatı psikanalitik açıdan değerlendirmek yerine; psikiyatrik vakalardan oluşan metni, edebî açıdan değerlendirmek amacındadır. Psikiyatrist Dr. Gülseren Budayıcıoğlu, hastalarının hikâyelerinden ve terapilerinden yola çıkarak öykü ve roman kurmacası içinde bunları okuyucuya sunmaktadır. Eserleri, kadın karakterlerini esas alarak edebî çözümlemeye tabi tutacağız. Yazarın ilk eseri Madalyonun İçi, kısa kısa öykülerden oluşur. İkinci eser Günahın Üç Rengi, temelde üç esas öykü barındırır. Üçüncü eseri Hayata Dön, romandır yine de içinde, kısa hasta vakaları yer alır. Bu eserlerde yazar, Doktor kimliğini açık eder, gerçeklik algısı daima açıktır. Dördüncü eser Kral Kaybederse’de teknik roman kurgusu oluşmuştur. Her eserde ön planda olan kadındır. Eserlerdeki kadınların aldığı hasarların psikolojilerine nasıl etki ettiği, yazarın psikiyatr olarak sorunlara yaklaşımı ve kadınlara, bu sorunlarla nasıl baş edebilecekleri konusunda yol göstericiliğini içerir.